Development Model of Loyalty and Customer Satisfaction Through Service Quality and Product Quality Ulamm Pantas at PT. Permodalan Nasional Madani Tangerang Branch Office - Erikson, Juan; Agus Salim (Dinasti Publisher, 2023)
This study aims to examine the effect of service quality, ULaMM PANTAS product quality on customer loyalty through customer satisfaction at PT. Permodalan Nasional Madani Tangerang Branch Office. This study uses a quantitative approach with Structural Equation Modeling (SEM) using the AMOS program. The unit of analysis used is all ULaMM Pantas customers of PT. Civil National Capital Branch of Tangerang which has done a minimum of two Top Ups. The sample consists of 300 respondents. Data collection techniques were carried out using online questionnaires. The results of the study prove that service quality and product quality have a positive and significant influence on customer satisfaction and loyalty. Customer satisfaction can mediate the effect of service and product quality on customer loyalty. The conclusion of this study is that the higher the customer satisfaction in mediating the quality of services and products, the higher the loyalty of ULaMM PANTAS customers to PT. Permodalan Nasional Madani Tangerang Branch Office.